1988
DOI: 10.1677/joe.0.1180279
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between prolactin, LH and broody behaviour in bantam hens

Abstract: The interactions between broody behaviour and changes in concentrations of plasma prolactin and LH were investigated in bantam hens. Adoption of newly hatched chicks caused incubating hens to leave their nests and prevented plasma prolactin decreasing as rapidly as in hens deprived of their nests and not given chicks. Further, the hens allowed to rear chicks came back into lay later (P less than 0.001) than the hens not allowed chicks. Plasma prolactin decreased and plasma LH increased in hens deprived of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
89
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 0 publications
13
89
3
Order By: Relevance
“…14 The latter finding is inconsistent with a direct role for PRL in clutch size determination. 15 We also found no evidence that individual variation in the magnitude and direction of 16 changes in LH were associated with changes in PRL, as would be predicted by a systemic 17 inhibitory effect of PRL on LH. Other studies have also not found evidence for inhibitory we would expect if these traits were mechanistically linked.…”
Section: Statistical Analysescontrasting
confidence: 58%
“…14 The latter finding is inconsistent with a direct role for PRL in clutch size determination. 15 We also found no evidence that individual variation in the magnitude and direction of 16 changes in LH were associated with changes in PRL, as would be predicted by a systemic 17 inhibitory effect of PRL on LH. Other studies have also not found evidence for inhibitory we would expect if these traits were mechanistically linked.…”
Section: Statistical Analysescontrasting
confidence: 58%
“…Still it is not fully elucidated that a change in the concentration of prolactin is responsible for timing of oviposition in domestic hen (Wentworth et al, 1983) or due to longer intervals of LH surges. Also prolactic plays a role in the development of broodiness in poultry with reference to turkey and bantam hens (Sharp et al, 1988) nothing is reported in this breed. The plant family Lamiaceae has received the greatest interest in poultry feed, with peppermint, thyme and oregano as the most popular representatives (Burt, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Broodiness basically means a hen sits on her eggs for the purpose of hatching the embryos. Physiologically, it has been well established that prolactin (PRL) plays an important role in the onset of incubation of hens (Sharp et al, 1988;March et al, 1994;Ohkubo et al, 1998). Increased plasma PRL concentration is associated with the occurrence of broodiness (Burke and Dennison, 1980;Bacon, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Cessation of egg laying is associated with increased concentrations of plasma prolactin (Etches, Garbutt, and Middleton, 1979;Burke and Dennison, 1980;Lea et al, 1981;Bluhm, Phillips, and Burke, 1983;Hall and Goldsmith, 1983;Silverin and Goldsmith, 1983), and in turkeys and domestic fowl (Sharp, Macnamee, Sterling, Lea, and Pedersen, 1988), administration of exogenous prolactin suppresses plasma gonadotropins necessary for egg production. However, there is additional evidence that the suppression of gonadotropin secretion in incubating birds also involves a mechanism independent of increased prolactin secretion (Sharp et al, 1988;Lea and Sharp, 1989;Sharp, Sterling, Talbot, and Huskisson, 1989;Lea, Richard-Yris, and Sharp, 1996).…”
mentioning
confidence: 99%